Experimental study on the flat-wise compression of foldcore sandwich paperboard. (December 2022) - E., Yuping; Yang, Guang; Zhu, Xianmei; Lu, Guoxing; Sun, Junjun
Abstract: Foldcore sandwich structures have aroused considerable research interest in recent years. While foldcores made of metal or composite have been studied extensively, paper-based foldcore are relatively rare. In this paper, we focus on the flat-wise compression properties of foldcore sandwich paperboard with the Miura-ori pattern in the field of packaging and logistics engineering. The flat-wise compression properties and affecting factors of foldcore sandwich paperboard are identified experimentally. Among these factors, the side length ratio ( a / b ) of the Miura-ori unit significantly influences the deformation mode of the foldcore sandwich paperboard, thus affecting the load-carrying performance and energy-absorption properties. Moreover, the foldcore sandwich paperboard is compared with the conventional corrugated paperboard. The results indicated that although the specific peak stress of foldcore sandwich paperboard and conventional B-flute corrugated paperboard are approximately equal at the same profile angle, the specific energy absorption of the former was 2.06 times higher than the latter. What is more, the specific peak stress and specific energy absorption of the foldcore sandwich paperboard are 1.93 times and 3.24 times higher than those of B-flute corrugated paperboard by merely increasing the sector angle from 60° to 75°. These findings may provide the potential for practical application of paper-based foldcore sandwich panels, thus facilitating the structural design of multilayered cushioning paper pads. Graphical abstract: Highlights: Flat-wise compression behaviors of paper-based foldcore sandwich structure were experimentally investigated. Side lengths ratio a/b was the critical factor that affects the deformation mode of the foldcore sandwich paperboard. Flat-wise compression performance of foldcore sandwich paperboard and conventional corrugated paperboard were compared. Energy absorption of foldcore sandwich paperboard were 2.06 times higher than corrugated paperboard with same profile angle. Load-carrying and energy-absorption properties of foldcore sandwich paperboard could be significantly improved with the increase of α .